1986
DOI: 10.1017/s0003356100017943
|View full text |Cite
|
Sign up to set email alerts
|

The response of store lambs to dietary supplements of fish meal 2. effects of level of feeding

Abstract: Forty-eight, individually-penned lambs (mean live weight 31·4 kg) were given diets with or without fish meal (0 and 90 g intake daily) in sufficient quantities to provide energy for maintenance and either 100, 150 or 200 g daily gain. Nitrogen (N) degradability in the rumen and fractional outflow rates of protein supplements were determined and the diets formulated such that the lambs received about 2·2 and 6·7 g undegradable rumen N daily on all three feeding levels.Live-weight gains were generally greater du… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

1988
1988
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 8 publications
0
6
0
Order By: Relevance
“…Similarly, no effect of fish meal on rate or efficiency of growth was reported by several researchers (Batchelder, 1987;Hussein and Jordan, 1991a;Villalba and Provenza, 2000). In contrast, rate and efficiency of lamb growth were improved by including fish meal in the diets in other experiments (Hassan and Bryant, 1986;Tan and Bryant, 1991;Walz et al, 1998). Stock et al (1983) also found that lambs gained faster and more efficiently when fed 14% CP corn-based diets with supplemental protein from blood meal rather than soybean meal.…”
Section: Source Of Protein Supplementsmentioning
confidence: 76%
See 1 more Smart Citation
“…Similarly, no effect of fish meal on rate or efficiency of growth was reported by several researchers (Batchelder, 1987;Hussein and Jordan, 1991a;Villalba and Provenza, 2000). In contrast, rate and efficiency of lamb growth were improved by including fish meal in the diets in other experiments (Hassan and Bryant, 1986;Tan and Bryant, 1991;Walz et al, 1998). Stock et al (1983) also found that lambs gained faster and more efficiently when fed 14% CP corn-based diets with supplemental protein from blood meal rather than soybean meal.…”
Section: Source Of Protein Supplementsmentioning
confidence: 76%
“…However, the extent of degradability is influenced by animal variation, other dietary ingredients, and feed processing. These may be some of the reasons that replacing soybean meal with fish meal has not given consistent results (Pond, 1984;Hassan and Bryant, 1986;Walz et al, 1998).…”
Section: Introductionmentioning
confidence: 99%
“…Fish meal offers a rich supply of rumen undegradable protein (UDP) and has been found to increase nitrogen retention (Hassan and Bryant, 1986). However, the linear growth responses up to the highest level of fish meal offered (140 g FW per head per day) were unexpected, particularly since ARC (1980) predicted that a source of UDP is unnecessary in lambs over 30 kg.…”
Section: Figmentioning
confidence: 99%
“…Lambs require undegradable feed protein to support high rates of growth and wool production (NRC, 1985). Fish meal ( FM) is an excellent source of highquality protein that is slowly degraded in the rumen (Amos et al, 1972;Adam et al, 1982;Zerbini and Polan, 1985), but the response in growth rate has been variable (Pond, 1984;Beerman et al, 1986;Hassan and Bryant, 1986;Hussein and Jordan, 1991a). The inconsistent response to feeding ruminally undegradable protein has been reviewed with emphasis on FM (Hussein and Jordan, 1991b).…”
Section: Introductionmentioning
confidence: 99%